(untitled) (City: History, Culture, Society, 2021)
Issues related to such areas of archaeological thanatology as the perception of death by ancient man, the evolution of funeral traditions and rituals have always been topical, both at the dawn of humanity and today. The problems of taphology, the branch of thanatology that studies the field of human activity related to the burial of dead members of society, remain relevant in modern archaeological science. When studying the problems of funeral rites, the researcher must understand its structure, be able to operate with a terminological system, correctly choose the appropriate methods for the adequate reconstruction of particular funeral practice. Unfortunately, a clear taphological structure has not yet been defined in national science, attempts to unify the conceptual apparatus have been sporadic and have not led to the formation of a single system of the specialized vocabulary of terms. This paper is an attempt to define the appropriate structure of the "science of burial" and to understand the terms that can be used in modern historical and archaeological sciences. Needless to say, the positive effects of studies in this area will at least help to avoid confusion in the names and concepts that are actively used in the study of funeral rites. Further development of the terminological apparatus will allow deepening the scientific and methodological aspects of studying the funeral rite as a unique process. The main issues related to the theory of taphology and the creation of an appropriate terminological apparatus are widely analyzed in the works of such well-known experts as V. Alyokshin, V. Henning, V. Gulyaev, A. Dobrolyubsky, I. Kizlasov, G. Lebedev, V. Melnyk, V. Nazarenko, V. Olkhovsky, Yu. Smirnov, S. Tokarev. For the structural and terminological basis of the research, we have chosen a unified system of terms by Yu. Smirnov in a complex combination with the creative works of other above-mentioned researchers. The composition of the basic terms is preliminary and looks forward to future additions and improvements. We consider this article as an invitation of specialists of different directions to the scientific discussion. The purpose of the discussion should be to determine a stable taphological structure and to create a terminological apparatus that can be used in modern historical and archaeological sciences in research related to funeral rites.